From Hus to Luther: visual culture in the Bohemian Reformation (1380-1620) - Horníčková, Kateřina; Šroněk, Michal (Medieval church studies, 2016)
This book portrays a little-known phenomenon in Bohemian cultural and political history - the visual culture that grew up in the environment of Reformation churches in Bohemia from the time of the Hussites until the defeat of the Estates by the Habsburg coalition at White Mountain in 1620. It provides the first comprehensive overview of a forgotten era of artistic production over a period of approximately two hundred years, when most of the population of Bohemia professed non-Catholic faiths. During the fifteenth and sixteenth centuries a unique situation arose in Bohemia, with five main Christian denominations (Utraquists, Lutherans, the Unity of Brethren, Calvinists, and Catholics) gradually coming to function alongside each other, with a number of other religious groups also active. The main churches, which had a fundamental influence on political stability in the state, were the majority Utraquists and the minority Catholics. Yet the essays of this book establish that despite the particularities of the Bohemian situation, the religious trends of Bohemia were an integral part of the process of Reformation across Europe. Featuring over fifty illustrations including manuscript illumination, panel painting, and architecture, the book also presents the surviving cultural products of the four non-Catholic Christian denominations, ranging from the more moderate to radical Reformation cultures. The book also analyses the attitudes of these denominations to religious representations, and illuminates their uses of visual media in religious and confessional communication